2006
DOI: 10.1007/s11104-006-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Grain 15N of crops applied with organic and chemical fertilizers in a four-year rotation

Abstract: Variations in crop grain and soil N isotope composition (d 15 N) in relation to liquid hog manure (d 15 N of total N was +5.1&), solid cattle manure (+7.9&) and chemical fertilizer (+0.7& for urea and )1.9& for ammonium phosphate) applications, and control (no fertilizer application) were examined through a 4-year crop rotation under field conditions. Canola (Brassica napus), hull-less barley (Hordeum vulgare), wheat (Triticum aestivum), and canola were grown sequentially from 2000 (year 1) to 2003 (year 4). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 31 publications
4
41
0
Order By: Relevance
“…Hog manure with a high content of NH 4 has been shown to be lower in 15 N than cattle manure dominated by organic N. [25] However, volatilized NH 3 is isotopically considerably lighter than the residual NH 4 retained in stored manure, and the d 15 N value of NH 4 extracted from stored cattle slurry has been found to be higher than values determined for total-N. [26] The d 15 N values of AM-treated soils from the B3-field (6.2 %) and the B5-field (6.8 %) were somewhat lower than values reported for manure by Choi and co-authors (7.9 %), [25] Watzka and co-authors (7.7 to 10.2%), [26] and Kriszan and co-authors (8.9 %), [28] but slightly higher than the average d…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Hog manure with a high content of NH 4 has been shown to be lower in 15 N than cattle manure dominated by organic N. [25] However, volatilized NH 3 is isotopically considerably lighter than the residual NH 4 retained in stored manure, and the d 15 N value of NH 4 extracted from stored cattle slurry has been found to be higher than values determined for total-N. [26] The d 15 N values of AM-treated soils from the B3-field (6.2 %) and the B5-field (6.8 %) were somewhat lower than values reported for manure by Choi and co-authors (7.9 %), [25] Watzka and co-authors (7.7 to 10.2%), [26] and Kriszan and co-authors (8.9 %), [28] but slightly higher than the average d…”
mentioning
confidence: 97%
“…[12,14,[25][26][27][28] However, the use of AM had a significant positive effect on soil total-N and d 15 N, and the soil d…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Most studies that tried to differentiate inorganic and organic fertilized crops found that plants treated with inorganic fertilizers have significantly lower δ 15 N values (BATEMAN et al, 2005;CHOI et al, 2006). Given the importance of inorganic fertilizers in modern agriculture, this should be taken into account when data derived from cultivated plants of modern research are used as basis for diet (KEEGAN;DENIRO, 1988;SZPAK et al, 2013;WARINNER et al, 2013).…”
Section: Variablesmentioning
confidence: 99%
“…Since the δ 15 N values of N 2 -fixing and non-N 2 -fixing plants have significant differences (Chang and Choi, 2009), the 15 N natural abundance technique is generally applied to analyzing the N processes between N 2 -fixing and non-N 2 -fixing plants and the N nutrient status among plant species (Matsushima and Chang, 2007). Van Choi et al (2006) Composted manure +14.6 ± 3.3 Eggplant, Hot pepper, Brassicas Choi et al (2003) found that a portion of the N 2 fixed by Leucaena leucocephala during the early stages of tree growth was made available to the understorey species through the decomposition and subsequent incorporation into the available soil-N pool of the abscissed L. leucocephala parts, which provided the direct evidence of internal N cycling between a N 2 -fixing tree and non-N 2 -fixing understorey species. Matsushima and Chang (2007) indicated that the Canada bluejoint grass (Calamagrostis canadensis) significantly reduced the δ 15 N in the foliar of the coplanted white spruce (Picea glauca), which was related to the causes that strong NH 4 + -N uptake by bluejoint might have prevented significant soil N losses and 15 N enrichment through nitrification and subsequent denitrification.…”
Section: Nitrogen Transformation Processes Of Ecosystemmentioning
confidence: 99%